KEHIDUPAN SOSIAL EKONOMI PETANI GULA MERAH DI DESA KALATIN KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA - Meyni Meflike Supit (Universitas Sam Ratulangi, 2022)
The development of the agricultural sector is often directed to be able to support the industrial sector that is sought to become a Resilient sector Due to the interrelationships between the agricultural and industrial sectors, industrial development. Agricultural products (agro-industry) are expected to increase the added value of agricultural products and expand job creation. Socioeconomic life is the position or position of a person in a group of people determined by the type of economic activity, education, as well as income. Farmers are those who for a time or remain in control of a piece of agricultural land, master a branch or several branches of a farm business and work on their own, either with their own labor or paid labor. Brown sugar has many benefits such as having a high calorie content, as a natural coloring in food, a high fiber content, so it is good for digestion and inhibits the absorption of cholesterol by the body. The southeast Minahasa Regency area is sloped and overgrown with palm trees, so the economic life of most people in Southeast Minahasa Regency, especially in Ratahan District, is a brown sugar farmer who processes palm juice into brown sugar. In the manufacturing process, palm sugar is generally more natural, so that certain substances contained in it are not damaged and remain intact and do not require the distillation process many times or use additional ingredients to purify it. Keywords : socioeconomic life, farmers, palm sugar